An investigation of kayak geometry and athlete performance in Olympic canoe slalom - Morris , S. C. (University of Nottingham, 2015)
The Olympic sport of Canoe Slalom relies heavily on the complex relationship between an athlete and their equipment, to complete a task in the shortest time possible, without occurring penalties, within a demanding white water environment. A successful slalom kayak is a compromise of forward speed, manoeuvrability and stability as defined by its physical form, allowing the athlete to maintain control in a race environment. The evolution of the slalom kayak has been slow and no set methodology exists to quantify and compare designs and their performance outputs. Slalom competitions are regularly lost by fractions of a second and as the sport relies heavily on equipment, it is imperative that an athlete has the optimal kayak to aid their performance. A questionnaire captured initial information regarding the British Canoe Slalom team athlete`s current boats and related performance. This data lead to a structured testing protocol being devised. A series of identical kayaks manufactured with four iterative form changes at three levels were laser scanned to capture their geometry from which hydrostatic and form analysis was carried out using CAD. Two athletes completed three field tests in the iterative kayak forms. Objective and subjective measures captured performance and the results were presented as a percentage of a control. Strathclyde Universities tow tank facility investigated the kayak forms outright steady state drag characteristics. The results showed that the methodology captured differences in kayak geometry and performance. Average performance time improvements of up to 1.94% were seen over the control kayak as well as decreases in performance of up to 12.4% due to differences in kayak form. The results indicated that athlete mass was an important factor in how a design performed and that different forms should be designed and selected for different athlete masses. This thesis produces a body of knowledge defining methodologies for the categorisation and analysis of slalom kayak form and methods for testing performance. This research will be beneficial to athletes, coaches, designers and manufacturers.